YTHDF2 Inhibits the Migration and Invasion of Lung Adenocarcinoma by Negatively Regulating the FAM83D-TGFβ1-SMAD2/3 Pathway - Zhao, Teng; Wang, Mingchao; Zhao, Xin; Weng, Shuang; Qian, Kun; Shi, Kejian; Gu, Yanfei; Ying, Wantao; Qian, Xiaohong; Zhang, Yi (Frontiers in Oncology, 2022)
Objective: YTHDF2 is an important N6-methyladenosine (m6A) reader, and its role in lung adenocarcinoma remains elusive. This study assessed its function in lung adenocarcinoma. Methods: YTHDF2 expression in lung adenocarcinoma was explored via public databases, such as The Cancer Genome Atlas (TCGA) and the Clinical Proteomic Tumor Analysis Consortium (CPTAC). The effect of YTHDF2 on a lung adenocarcinoma cell line was explored by cytological and molecular experiments. Molecules downstream of YTHDF2 were identified by proteomics, and the related pathways were verified through cytological and molecular biology experiments. Results: YTHDF2 expression was upregulated in lung adenocarcinoma, and patients with high YTHDF2 expression had better overall survival. In two lung cancer cell lines, YTHDF2 knockdown inhibited proliferation but promoted migration, invasion, and epithelial-mesenchymal transition. Proteomic analysis revealed 142 molecules downstream of YTHDF2, and 11 were related to survival. Further study revealed that YTHDF2 inhibited the expression of FAM83D-TGFβ1-SMAD2/3 pathway components. This is the first time that YTHDF2 has been found to regulate the downstream TGFβ1-SMAD2/3 pathway through FAM83D in lung adenocarcinoma. Conclusion: YTHDF2 inhibits the migration and invasion of lung adenocarcinoma cells by regulating the FAM83D-TGFβ1-pSMAD2/3 pathway, which may play an important role in lung cancer metastasis.